On the Performance of SVD-DWT Based Digital Video Watermarking Technique with Semi-Blind Detector - Basaruddin, Tarzan; Maulidiya, Della (UI Scholars Hub, 2009)
On the Performance of SVD-DWT Based Digital Video Watermarking Technique with Semi-Blind Detector. This paper presents a watermarking technique for digital video. The proposed scheme is developed based on the work of Ganic and Chan which took the virtue of SVD and DWT. While the previous works of Chan has the blind detector property, our attempt is to develop a scheme with semi-blind detector, by using the merit of the DWT-SDV technique proposed by Ganic which was originally applied to still image. Overall, our experimental results show that our proposed scheme has a very good imperceptibility and is reasonably robust especially under several attacks such as compression, blurring, cropping, and sharpening.